The Potential of Green Development and PM2.5 Emission Reduction for China’s Cement Industry - Li Tian (Atmosphere, 2023)
The atmospheric dust caused by the cement industry is one of the main components of air pollutants. China is the largest producer and consumer of cement. It is challenging to balance cement needs and environmental protection. Based on the emission source data, this study examined the spatial and temporal patterns of PM2.5 by the cement industry’s contribution (PM2.5Cement). The annual value of PM2.5Cement decreased from 1.40 × 106 µg/m3 in 2010 to 0.98 × 106 µg/m3 in 2017, which was reduced by 30.31%. I used the standard deviation ellipse and gravity center transfer method and identified that the cement industry center shifted from the east to the midwest of China, where a high-density population exists and a large portion of the population is exposed to the air pollution. The geographical detector method was used to analyze the contribution of the natural environment, green development, and socioeconomic development to PM2.5Cement. The main driving factors were identified as the socioeconomic development and the traffic conditions in 2010, which was giving way to the regional independent innovation in 2017. The cement industry’s contributions to atmospheric PM2.5 vary spatially, suggesting that green development and optimized location for the cement industry are crucial to reducing the size of the population exposed to the pollutants.